2010
DOI: 10.1186/1742-4755-7-7
|View full text |Cite
|
Sign up to set email alerts
|

Access to infertility services in Canada for HIV-positive individuals and couples: a cross-sectional study

Abstract: BackgroundFamily and pregnancy planning issues are important among human immunodeficiency virus (HIV)-positive individuals and couples. However, access to fertility services may be limited for this population. The objective of this study was to estimate the types of services available in fertility clinics in Canada for these individuals.MethodsA survey was sent to all registered fertility clinics in Canada to assess the availability of services (investigations and treatment) for infertility and/or viral transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 21 publications
0
34
1
1
Order By: Relevance
“…Inadequate access to conception planning and assisted reproductive services has been documented in North America, Australia and the United Kingdom, despite the existence of guidelines for reproductive care for PLWHIV (Apoola et al, 2001;Cooper et al, 2009;Frodsham, Boag, Barton, & Gilling-Smith, 2006;Gruskin, Firestone, MacCarthy, & Ferguson, 2008;Minkoff, 2006;Pitts & Shields, 2004;Sauer, 2006;Stanitis, Brow, & Wiczyk, 2008;Yudin, Shapiro, & Loutfy, 2010). Our study showed that although 63% of participants intended a future pregnancy and 44% had a plan for conception in the near future, only 30% had spoken to an HCP about the issue and only 30% had some knowledge about conception planning and assisted reproductive services for safer conception.…”
Section: Discussioncontrasting
confidence: 57%
“…Inadequate access to conception planning and assisted reproductive services has been documented in North America, Australia and the United Kingdom, despite the existence of guidelines for reproductive care for PLWHIV (Apoola et al, 2001;Cooper et al, 2009;Frodsham, Boag, Barton, & Gilling-Smith, 2006;Gruskin, Firestone, MacCarthy, & Ferguson, 2008;Minkoff, 2006;Pitts & Shields, 2004;Sauer, 2006;Stanitis, Brow, & Wiczyk, 2008;Yudin, Shapiro, & Loutfy, 2010). Our study showed that although 63% of participants intended a future pregnancy and 44% had a plan for conception in the near future, only 30% had spoken to an HCP about the issue and only 30% had some knowledge about conception planning and assisted reproductive services for safer conception.…”
Section: Discussioncontrasting
confidence: 57%
“…Healthcare providers ought to consider adding a discussion about pregnancy planning, healthy pre-conception lifestyle, and contraception into routine HIV care to support safer pregnancies, maximizing the health of the women and their partners and protecting future children by reducing vertical transmission. In Canada, we are in the process of developing national guidelines on pregnancy planning as well as provincial and national HIV Fertility Programs [20,30,31]. We hope that our research and ongoing projects will assist HIV-positive individuals, policy makers and healthcare providers globally to develop their programmes for safer, supportive pregnancy and family planning for HIV-positive individuals in their communities.…”
Section: Discussionmentioning
confidence: 99%
“…However, access to reproductive treatment has been controversial, with few clinics globally engaging in practices to support this patient group (Yudin et al, 2010). It is therefore probable that many serodiscordant couples have unmet desires around their family intentions due to the scarcity of such programmes.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence also exists regarding differences between the fertility desires of positive men and women, with many studies finding that men were more likely to continue to desire children after they had learned about their HIV-positive status (Paiva, Filipe, Santos, Lima, & Segurado, 2003). While HIV requires individual adjustment and lifestyle modifications, it does not remove or eradicate the desire for a child or a family (Yudin, Shapiro, & Loufty, 2010).…”
Section: Introductionmentioning
confidence: 97%